3D dynamic response of a multi-layered transversely isotropic half-space subjected to a moving point load along a horizontal straight line with constant speed. (1st December 2016) - BA, Zhenning; Liang, Jianwen; Lee, Vincent W.; Ji, Hang
Abstract: The steady-state dynamic response of a multi-layered transversely isotropic (TI) half-space generated by a point load moving along a horizontal straight line with constant speed is investigated in this paper. To solve this problem, the direct stiffness method combined with the inverse Fourier transform is employed. First, the dynamic equilibrium equations for the TI medium are solved in the frequency and wavenumber domains and the exact three-dimensional (3D) dynamic stiffness matrix for the layered TI half-space is established. Then, the solution in the frequency and wavenumber domains is obtained through the direct stiffness method. Finally, the dynamic response in the time and space domains is obtained using the double inverse Fourier transform with respect to the frequency and one horizontal wavenumber. The accuracy of the method is verified through comparisons with the results for the limiting isotropic case (de Barros and Luco, 1994 ) as well as the results for the non-moving 3D point load being applied in a multi-layered TI half-space (Khojasteh et al., 2011 ). Numerical results for both the uniform TI half-space and multi-layered TI half-space are presented, and the effects of the moving speed and especially the material anisotropy on the dynamic response are analyzed. Numerical results show that the dynamic response in a TI medium can be significantly different from that in an isotropic medium, and material anisotropy is very important for the accurate assessment of the dynamic response due to a point load moving in a TI half-space.